Systemic inflammatory response syndrome in diseases of the skin. Issue 1012 (9th February 2010) - Thomas, Molly; Peter, John Victor; Williams, Abhilasha; Job, Victoria; George, Renu
Abstract : Background: A number of dermatological conditions present with features of systemic inflammatory response syndrome (SIRS). This study evaluated the incidence and outcome of SIRS in patients with dermatological diseases. Study design: Prospective cohort study. Results: Patients admitted to a university hospital with a skin disease and fulfilling at least two SIRS criteria were included. The primary outcome measure was mortality. Secondary outcomes included incidence of multiple organ dysfunction syndrome (MODS), sepsis, severe sepsis and shock. Over 14 months, 2765 inpatients with skin related problems were examined. These included 721 patients admitted directly to the dermatology ward and 2044 patients referred from other departments within the hospital, with cutaneous manifestations. The incidence of SIRS in this cohort was 2.4% (n=67). The mean (SD) age was 32.6 (19.7) years with a male:female ratio of 1.2:1. Cutaneous adverse drug reaction (CADR) was the most common cause of SIRS (35.8%). During hospitalisation, 37 patients (55.2%) developed sepsis, 23 (34.4%) MODS, 15 (22.4%) severe sepsis and 6 (9%) shock. Methicillin sensitive Staphylococcus aureus was the most common skin isolate (41.4%) and Enterococcus the most common blood isolate. Overall mortality was 15% (10/67). Older age, low albumin, MODS, severe sepsis and shock were associated with an increased risk of death (p<0.03). Positive blood cultures, liver or lung involvement were also significantly associated with increased mortality (p<0.01). Conclusion: The incidence of SIRS was low in dermatological diseases. In this cohort, CADR was the most common cause of SIRS. Patients who developed sepsis or MODS had a poor outcome.